Perbedaan Tingkat Kecemasan Pasien Pre Operasi Sebelum dan Setelah diberikan Intervensi Teknik Relaksasi Otot Progresif Kombinasi Nafas Dalam: Differences Anxiety Levels in Preoperatif Patients Before and After Given Progressive Muscle Relaxation Technique Combine with Deep with Deep Breating Intervention - Yunita Galih Yudanari; Feby Purnamasari; Faridah Aini (Jurnal Keperawatan Berbudaya Sehat, 2026)
Major surgery is a medical procedure that requires both mental and physicalpreparation as it can trigger anxiety. This anxiety may arise during the preoperative, intra-operative, and post-operative phases, necessitating appropriatenursing care. Progressive muscle relaxation (PMR) and deep breathing arenursing interventions aimed at reducing anxiety by relaxing tense muscles andenhancing comfort. This study aims to determine the difference in anxiety levelsamong pre-operative patients before and after being administered a combinationof progressive muscle relaxation and deep breathing techniques. The researchdesign is a quasi-experimental study using a one-group pre-test and post-testdesign. The sample consisted of 46 participants selected through purposivesampling. The research instrument used was the Amsterdam Pre-OperativeAnxiety and Information Scale (APAIS) questionnaire. The results showed thatthe average anxiety level scores decreased after the implementation of thecombined progressive muscle relaxation and deep breathing techniques, with ap-value of 0.000 (< 0.05). This indicates a significant difference between the pretest and post-test values. In conclusion, there is a significant difference in anxietylevels among pre-operative patients before and after the intervention. Widerapplication of this intervention is recommended for pre-operative patientsexperiencing anxiety.